2004
DOI: 10.1016/j.bbapap.2004.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Structure/function analyses of human serum paraoxonase (HuPON1) mutants designed from a DFPase-like homology model

Abstract: and Cerasoli, Douglas M., "Structure/function analyses of human serum paraoxonase (HuPON1) mutants designed from a DFPaselike homology model" (2004 AbstractHuman serum paraoxonase (HuPON1) is a calcium-dependent enzyme that hydrolyzes esters, including organophosphates and lactones, and exhibits anti-atherogenic properties. A few amino acids have been shown to be essential for the enzyme's arylesterase and organophosphatase activities. Until very recently, a three-dimensional model was not available for HuPON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 37 publications
(63 reference statements)
6
73
0
Order By: Relevance
“…Mutagenesis experiments supported the suggested mechanism, although it was later found that these mutants were probably misfolded and therefore inactive (13). Moreover, Yeung et al (14) recently reported that the H115W mutant of human PON1 retains activity with paraoxon. They therefore postulated that His 115 is important for substrate binding and specificity, but does not directly participate in catalysis (15).…”
Section: Serum Paraoxonases (Pons)mentioning
confidence: 64%
See 1 more Smart Citation
“…Mutagenesis experiments supported the suggested mechanism, although it was later found that these mutants were probably misfolded and therefore inactive (13). Moreover, Yeung et al (14) recently reported that the H115W mutant of human PON1 retains activity with paraoxon. They therefore postulated that His 115 is important for substrate binding and specificity, but does not directly participate in catalysis (15).…”
Section: Serum Paraoxonases (Pons)mentioning
confidence: 64%
“…The mutation of His 115 , which is important for hydrolysis of lactones and esters (14,15), did not have much effect on the phosphotriesterase activity of PON1. The mutations of His 184 caused a Ͼ10-fold decrease in this activity, but there is no other evidence that ascribes a role for His 184 in catalysis.…”
Section: Non-detrimental Effect Of Mutations On Pon1mentioning
confidence: 99%
“…Notably, the active sites of DFPase and PON possess a conserved arrangement of amino acids around the catalytic calcium and, like DFPase, PON also shows activity against selected organophosphate triesters (22,23).…”
mentioning
confidence: 99%
“…Furthermore, CD spectra of purified tag-free E3 showed a broad minimum centered around 210 nm with a crossover point of 205 nm (Figure 2-8), in a good agreement with known β-fold proteins such as diisopropylfluorophosphatase 53,56 . And compared with wild type huPON1, E3 has 70 the negative peak shifted from 217 to 210 nm, indicating less composition of α-helices 57 . The enzymatic kinetics of tag-free E3 was also measured toward C4-HSL and C6-HSL.…”
Section: Generation Of Soluble Expressed Hupon2 Variantsmentioning
confidence: 91%